Coastal Ocean and Nearshore Observation: A French Case Study - Cocquempot, Lucie; Delacourt, Christophe; Paillet, Jérôme; Riou, Philippe; Aucan, Jérôme; Castelle, Bruno; Charria, Guillaume; Claudet, Joachim; Conan, Pascal; Coppola, Laurent; Hocdé, Régis; Planes, Serge; et al. (Frontiers in Marine Science, 2019)
To understand and predict the physical, chemical, and biological processes at play in coastal and nearshore marine areas requires an integrated, interdisciplinary approach. This case study of the French structuration of coastal ocean and nearshore observing systems provides an original overview on a federative research infrastructure named ILICO. It is a notable example of national structuration and pan-institution efforts to investigate the forefront of knowledge on the processes at work within the critical coastal zone. ILICO comprises, in a pluridisciplinary approach, eight distributed network-systems of observation and data analysis that are accredited and financially supported by French research institutions and the French Ministry for Higher Education, Research, and Innovation. ILICO observation points are implemented along metropolitan and overseas French coasts, where coastline dynamics, sea level evolution, physical and biogeochemical water properties, coastal water dynamics, phytoplankton composition, and health of coral reefs are monitored in order to address a wide range of scientific questions. To give an overview of the diversity and potential of the observations carried out, this paper offers a detailed presentation of three constituting networks: SOMLIT, with homogeneous sampling strategies, DYNALIT, with heterogeneous sampling strategies adapted to different environments, and MOOSE, an integrated, pluri-disciplinary coastal/offshore regional observatory in the north-western Mediterranean Sea. ILICO was conceived using a European framework. It addresses the great challenges of the next decade in terms of sustainability, cost-efficiency, interoperability, and innovation. This paper emphasizes the added-value of federating these systems, and highlights some recommendations for the future.